Climate finance for resilience future: pioneering steps of the United Arab Emirates (UAE) in the Gulf region - Moussaid, Fatima zahra; Mohd Zain, Nor Razinah; Tounchibine, Oumaima; Ng, See Teong (Springer Nature, 2025)
Climate change presents a main challenge worldwide which requires urgent actions from different stakeholders. The integration of Islamic finance into discussions surrounding environmental sustainability emerges as a promising avenue for effective actions. In the Gulf region, known for its dominance in oil and gas production, countries play a dual role as both major contributors to climate challenges and key participants in global climate action efforts. Looking forward to 2025, the United Arab Emirates (UAE) emerges as a leader in climate action, demonstrating a notable emphasis on climate financing initiatives. This study employs a qualitative research methodology, utilizing a combination of library-based approaches and documentary analysis, to explore the complex intersections between climate finance, Islamic finance, and environmental sustainability within the UAE. Through an analysis of strategic approaches to climate financing in the country, incorporating Islamic finance, the study aims to elucidate the significance of environmental sustainability and its impact on climate mitigation practices adopted in the UAE. The findings highlight the importance of strategic approaches to climate finance among Islamic financial services providers in enhancing climate mitigation practices within the UAE. To this end, tailored Shariah-compliant instruments must be developed, while simultaneously fostering awareness, building capacity, and promoting strategic partnerships between relevant government entities and private sectors. By doing so, the best practices observed in the UAE demonstrate the potential for Islamic finance to emerge as a leading provider of climate finance, thereby advancing environmental sustainability goals.